Pembrolizumab for advanced urothelial carcinoma: exploratory ctDNA biomarker analyses of the KEYNOTE-361 phase 3 trial - Powles, Thomas; Chang, Yen-Hwa; Yamamoto, Yoshiaki; Munoz, Jose; Reyes-Cosmelli, Felipe; Peer, Avivit; Cohen, Graham; Yu, Evan Y.; Lorch, Anja; Bavle, Abhishek; Homet Moreno, Blanca; Markensohn, Julia; et al. (Nature medicine, 2024)
Circulating tumor DNA (ctDNA) is emerging as a potential biomarker in early-stage urothelial cancer, but its utility in metastatic disease remains unknown. In the phase 3 KEYNOTE-361 study, pembrolizumab with and without chemotherapy was compared with chemotherapy alone in patients with metastatic urothelial cancer. The study did not meet prespecified efficacy thresholds for statistical significance. To identify potential biomarkers of response, we retrospectively evaluated the association of pre- and posttreatment ctDNA with clinical outcomes in a subset of patients who received pembrolizumab ( n = 130) or chemotherapy ( n = 130) in KEYNOTE-361. Baseline ctDNA was associated with best overall response (BOR; P = 0.009), progression-free survival ( P < 0.001) and overall survival (OS; P < 0.001) for pembrolizumab but not for chemotherapy (all; P > 0.05). Chemotherapy induced larger ctDNA decreases from baseline to treatment cycle 2 than pembrolizumab; however, change with pembrolizumab ( n = 87) was more associated with BOR ( P = 4.39 × 10 −5 ) and OS ( P = 7.07 × 10 −5 ) than chemotherapy ( n = 102; BOR: P = 1.01 × 10 −4 ; OS: P = 0.018). Tumor tissue-informed versions of ctDNA change metrics were most associated with clinical outcomes but did not show a statistically significant independent value for explaining OS beyond radiographic change by RECIST v.1.1 when jointly modeled (pembrolizumab P = 0.364; chemotherapy P = 0.823). These results suggest distinct patterns in early ctDNA changes with immunotherapy and chemotherapy and differences in their association with long-term outcomes, which provide preliminary insights into the utility of liquid biopsies for treatment monitoring in metastatic urothelial cancer. Clinical trial registration: NCT02853305 . In an exploratory analysis of the KEYNOTE-361 phase 3 trial that tested immunotherapy and chemotherapy in advanced urothelial carcinoma, different early circulating tumor DNA (ctDNA) dynamics were observed between the two treatments, and ctDNA levels were associated with response to pembrolizumab but not to chemotherapy.